2010
DOI: 10.5120/1582-2119
|View full text |Cite
|
Sign up to set email alerts
|

OPTICS on Sequential Data: Experiments and Test Results

Abstract: The Web has enormous, various and knowledgeable data for data mining research. Clustering web usage data is useful to discover interesting patterns pertaining to user traversals, behaviour and their usage characteristics. Moreover, users accesses web pages in an order in which they are interested and hence incorporating sequence nature of their usage is crucial for clustering web transactions. In this paper we present OPTICS ("Ordering Points To Identify the Clustering Structure") algorithm to find density bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Their results revealed that each of the clusters contained observations with specific common characteristics and improved the algorithm efficiency by identifying the initial cluster centers. Santhisree & Damodaram (2010) presented an algorithm named OPTICS ("Ordering Points To Identify the Clustering Structure") to find density based clusters on the web usage data from the MSNBC.COM website. The average of inter cluster and intra cluster distance was calculated and the results were then compared with different similarity measures like Euclidean, Jaccard, projected Euclidean, cosine and fuzzy similarity to find the similarity between clusters and the results were visualized graphically to predict the user behaviour.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Their results revealed that each of the clusters contained observations with specific common characteristics and improved the algorithm efficiency by identifying the initial cluster centers. Santhisree & Damodaram (2010) presented an algorithm named OPTICS ("Ordering Points To Identify the Clustering Structure") to find density based clusters on the web usage data from the MSNBC.COM website. The average of inter cluster and intra cluster distance was calculated and the results were then compared with different similarity measures like Euclidean, Jaccard, projected Euclidean, cosine and fuzzy similarity to find the similarity between clusters and the results were visualized graphically to predict the user behaviour.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The OPTICS is a density-based algorithm that starts at a randomly selected node and expands towards the most data-intensive region, eventually organizes all nodes into an ordered sequence, and then clusters different nodes (Ankerst et al, 1999).Thus, the algorithm is widely used in many fields. K. Santhisree (2010) applied OPTICS to the text data clustering. WangPin, HuangYan (2011) use the improved algorithm OPTICS clustering MPSK/MAPSK signal constellation.…”
Section: Introductionmentioning
confidence: 99%